THE PERFORMANCE OF BANKS IN INDIA AFTER BANKING SECTOR REFORMS - Bala, Mukesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The banking sector in India has undergone significant transformations since the implementation of banking sector reforms, in the early 1990s. These reforms, aimed at improving the efficiency, competitiveness, and financial health of banks, have had a substantial impact on the performance of Indian banks. This paper reviews, the performance of banks in India post-reforms, with a focus on profitability, asset quality, capital adequacy, and operational efficiency. The review also explores the challenges faced by banks, particularly in the context of non-performing assets (NPAs), regulatory changes, and the increasing role of digital banking. The paper synthesizes relevant studies and, empirical evidences to provide a comprehensive overview of the effects of banking reforms on the Indian banking system.